2021
DOI: 10.1164/rccm.201909-1687oc
|View full text |Cite
|
Sign up to set email alerts
|

High Pleural Pressure Prevents Alveolar Overdistension and Hemodynamic Collapse in Acute Respiratory Distress Syndrome with Class III Obesity. A Clinical Trial

Abstract: Rationale: Obesity is characterized by elevated pleural pressure (P PL) and worsening atelectasis during mechanical ventilation in patients with acute respiratory distress syndrome (ARDS). Objectives: To determine the effects of lung recruitment maneuver (LRM) in the presence of elevated P PL on hemodynamics, left and right ventricular pressures and pulmonary vascular resistance. We hypothesized that elevated P PL protects the cardiovascular system against high airway pressures and prevents lung overdistension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Accordingly, in this issue of the Journal , to evaluate the hemodynamic consequences of higher levels of airway pressure in obese patients with acute respiratory distress syndrome (ARDS), De Santis Santiago and colleagues (pp. 575–584 ) ( 3 ) performed clinical and animal studies to determine if higher positive end-expiratory pressure (PEEP) can improve gas exchange without compromising hemodynamics.…”
mentioning
confidence: 99%
“…Accordingly, in this issue of the Journal , to evaluate the hemodynamic consequences of higher levels of airway pressure in obese patients with acute respiratory distress syndrome (ARDS), De Santis Santiago and colleagues (pp. 575–584 ) ( 3 ) performed clinical and animal studies to determine if higher positive end-expiratory pressure (PEEP) can improve gas exchange without compromising hemodynamics.…”
mentioning
confidence: 99%
“…Hypotension and hemodynamic stability have been a major clinical concern when high airway pressures are applied. In a recent study, De Santis Santiago et al ( 32 ) showed that levels of airway pressure that oppose high pleural pressure are well-tolerated hemodynamically in patients with class III obesity and recruitable lungs.…”
Section: Discussionmentioning
confidence: 99%
“…In this group, the high prevalence of complete airway closure (> 41%), can make driving pressures unreliable [ 104 ]. Furthermore, the hemodynamic tolerance to high PEEP was found remarkably good in class III obese patients (mean BMI = 57 kg/m 2 ) [ 105 ]. The technique is largely neglected in daily practice, likely due to technical challenges.…”
Section: Ecmo Versus Conventional Managementmentioning
confidence: 99%